Sierra Leone - Mining Sector Reform : A Strategic Environmental and Social Assessment - World Bank (Washington, DC, 2012)
The Strategic Environmental and Social Assessment (SESA) of the mining sector in Sierra Leone was undertaken in response to the Government of Sierra Leone's (GOSL) request for assistance in developing its minerals policy. The SESA will help meet long-term country development by integrating environmental and social considerations in mining sector reforms. The crucial aspect of the SESA process is that the environmental and social priorities for mining reforms were identified by stakeholders in the four regions of the country. This report, the culmination of a sequence of workshops and analytic work, provides a summary of the findings of the SESA process and makes recommendations on the policy, institutional, and governance changes required addressing environmental and social priorities in reform of the Sierra Leone mining sector. The SESA pays particular attention to political economy issues such as the potential capture or watering down of reforms by groups having vested interests or the danger of selective implementation of new policies and regulations due to pressure from powerful interest groups. It helps to identify innovative solutions to some of the potential problems and the limitations of new mining policies in a situation where institutional and governance capacity are likely to be weak for some time.